Bacteriological Profile and Safety of Chicken Broiler Meat Cuts - Abdellatief Abdelrahman, Hosny; Hussien Ismail, Takwa; Galal Elsayed Saleh, Norhan; Ibrahim Hussein Ahmed, Nada (Journal of Advanced Veterinary Research, 2022)
Fifty samples each of fresh chicken fillet, shiesh, drum, shawarma, and wings were collected from a poultry processing plant, in Ismailia city, Egypt. The values of the mean total bacterial counts were 2x104±7x102, 2x104±102, 1x104 ±3x102, 7x104±5x102, and 6x103±2x102 respectively, for total coliform counts were 2x10-2±4x10-1, 1x10-2±3x10-1, 5x10-2±2x10-1, 8x10-2±4x10-1, and3x10-2±1x10-1, respectively. The mean value of Staphylococcus aureus count in fillet was 2x10-2±2x10-1, in drum 1x10-2±3x10-1, shiesh 2x10-2±5x10-1, shawerma 2x10-2±10-1, and wings 4x10-1±10-1. For E. coli count in fillet was 9x10-1±0.4x10-1, in drum 2x10-1±0.2x10-1, in shiesh 2x10-1±0.6x10-1, in shawerma 1x10-1±0.2x10-1, and in wings was 1x10-1±0.1x10-1. The prevalence of Salmonella spp.in the examined chicken fillet, drum, shiesh, shawarma, and wings were 6%, 8%, 6%, 6%, and 4%, respectively. The results showed that E. coli could be detected in all samples and laid within the accepted limits for fillet, drum, shiesh, shawerma, and wings. The Standard limits (SE) recommended by The Egyptian Organization for standardization (EOS) for Salmonella revealed that chicken broiler cut exceeded the accepted limits with 3(6%) for fillet, 4(8%) for drum, 3(6%) for shiesh, 3(6%) for shawerma, and 2(4%) for wings. For total aerobic plate count, the samples which exceed the SE limits were 4(8%) for fillet, 5(10%) for drum, 6(12%) for Shiesh,7(14%) for shawerma, and 4(8%) for Wings. The results showed that the processing techniques applied, type of packing, poultry abattoirs, and the farm environment need an effective procedure to produce safe chicken broiler meat cuts.